2015
DOI: 10.20510/ukjpb/3/i1/89220
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Antibacterial Activity of Clove and Rosemary Essential Oils on Multidrug Resistant Bacteria

Abstract: The essential oils of Syzygium aromaticum (clove bud) and Rosmarinus officinalis L. (rosemary) were obtained by hydro-distillation. The antimicrobial activity of  clove bud oil and rosemary oil was investigated by agar well diffusion method against four multidrug resistant strains namely Acinetobacter baumannii, Pseudomonas aeruginosa, Staphylococcus aureus and Enterococcus feacalis as well as two standard strains, Staphylococcus aureusATCC29213 and Pseudomonas aeruginosaATCC27853. Both essential oils exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 0 publications
3
13
0
1
Order By: Relevance
“…The results from the agar disc diffusion method revealed that clove oil had inhibitory effects against all test MDR S. suis isolates. This is consistent with previous studies [33][34][35][36]. Incidentally, regarding the inhibition zones obtained from the essential oil, it is notable that differences can occur among studies due to the methods used in solubilizing the oils to obtain hydrophilic molecules [33], antimicrobial assays, and tested organisms.…”
Section: Discussionsupporting
confidence: 90%
“…The results from the agar disc diffusion method revealed that clove oil had inhibitory effects against all test MDR S. suis isolates. This is consistent with previous studies [33][34][35][36]. Incidentally, regarding the inhibition zones obtained from the essential oil, it is notable that differences can occur among studies due to the methods used in solubilizing the oils to obtain hydrophilic molecules [33], antimicrobial assays, and tested organisms.…”
Section: Discussionsupporting
confidence: 90%
“…BHOWMIK et al (2012) reported similar chemical compositions and KAPADIYA et al (2018) pointed out that eugenol was the main component in essential oils from S. aromaticum. This compound has been associated with high antioxidant (CORTÉS-ROJAS et al, 2014;GÜLÇIN et al, 2018) and antimicrobial activity (NAVEED et al, 2013;HUSSEIN et al, 2014;ABDULLAH et al, 2015;PUŠKÁROVÁ et al, 2017).…”
Section: Chemical Composition Of the Essential Oilsmentioning
confidence: 99%
“…Although, some researchers have already suggested that, as starter cultures, lactic acid bacteria were relatively resistant to the toxic effects of some essential oils, others advocate that the application of EO doses enough to control pathogenic bacteria could negatively affect the growth and survival of starter cultures comprising lactic acid bacteria; they also speculate about a potential decrease in acid production, which could affect the proper sensory characteristics and safety of the products (CARVALHO et al, 2015). The essential oil from S. aromaticum presented antimicrobial activity against S. aureus (NAVEED et al, 2013;HUSSEIN et al, 2014;ABDULLAH et al, 2015;PUŠKÁROVÁ et al, (2017), E. coli (NAVEED et al, 2013;PUŠKÁROVÁ et al, 2017) and Salmonella spp (NAVEED et al, 2013;PUŠKÁROVÁ et al;. NAVEED et al 2013 antibacterial activity of C. citratus oil and evidenced a clear growth-inhibition zone (>18mm) formed by E. coli, Staphylococcus aureus and Salmonella tiphi.…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds may inactivate the essential enzymes, react with the cell membrane activity, or disturb the genetic material functionally and disturb energy production and structural component synthesis (Celikel and Kavas, 2008). Diameters of the inhibition zones of essential oils S. Tural, S. Turhan and their mixtures vary according to their components (Abdullah et al, 2015) and bacteria strains (Lambert et al, 2001). The higher antimicrobial activity of TEO could be attributed to its thymol content, a monoterpene with a phenolic ring (Miladi et al, 2013).…”
Section: Antimicrobial Activitymentioning
confidence: 99%